2016
DOI: 10.1530/edm-15-0138
|View full text |Cite
|
Sign up to set email alerts
|

Is radioiodine administration in patients with papillary thyroid multifocal microcarcinoma unnecessary?

Abstract: SummaryRadioiodine (RAI) has played a crucial role in differentiated thyroid cancer treatment for more than 60years. However, the use of RAI administration in patients with papillary thyroid microcarcinoma (even multifocal) is now being widely discussed and often not recommended. In accordance with European consensus, and contrary to the American Thyroid Association (ATA) guidelines, we recently performed RAI thyroid remnant ablation in a patient with differentiated papillary multifocal microcarcinoma. The pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A higher percentage of soft tissue invasion and distant metastasis in multifocal PTMC are part of reasons with poor prognosis than that in solitary PTMC. The use of 131 I ablation for the treatment of multifocal PTMC is questioned by the European consensus and American Thyroid Association (ATA) guidelines [ 18 , 20 ]. In our study, 3.4% of multifocal PTMC had distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher percentage of soft tissue invasion and distant metastasis in multifocal PTMC are part of reasons with poor prognosis than that in solitary PTMC. The use of 131 I ablation for the treatment of multifocal PTMC is questioned by the European consensus and American Thyroid Association (ATA) guidelines [ 18 , 20 ]. In our study, 3.4% of multifocal PTMC had distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…BRAF gene mutation combined with X chromosome inactivation analyses has been used to evaluate the clonal origins of tumors and has showed that bilateral, recurrent, and metastatic PTCs often arise from a single clone and that intrathyroid metastasis may play an important role in the development of bilateral tumors [ 21 ]. In contrast, assessment of multifocal thyroid tumors using genetic alteration analyses and miRNA profiling found that multifocal PTC did not necessarily evolve from single PTC progenitor foci [ 20 ]. In the clinic, different histological patterns like follicular variant and classical PTC in different thyroid lobes are not unusual.…”
Section: Discussionmentioning
confidence: 99%